2015
DOI: 10.1155/2015/201625
|View full text |Cite
|
Sign up to set email alerts
|

KLF15 and PPARαCooperate to Regulate Cardiomyocyte Lipid Gene Expression and Oxidation

Abstract: The metabolic myocardium is an omnivore and utilizes various carbon substrates to meet its energetic demand. While the adult heart preferentially consumes fatty acids (FAs) over carbohydrates, myocardial fuel plasticity is essential for organismal survival. This metabolic plasticity governing fuel utilization is under robust transcriptional control and studies over the past decade have illuminated members of the nuclear receptor family of factors (e.g., PPARα) as important regulators of myocardial lipid metabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 56 publications
(100 reference statements)
1
48
0
Order By: Relevance
“…For example, in adipocytes, KLF5 cooperates with PPARδ to induce transcription of the Pparg2 gene and, in doing so, promotes adipogenesis (21,41). In cardiomyocytes, KLF15 cooperates with PPARα in regulating lipid metabolism (42). Conversely, activation of GR signaling can induce a number of KLFs (e.g., KLF9, KLF11, and KLF15) in specific physiologic or pathologic contexts (43)(44)(45).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in adipocytes, KLF5 cooperates with PPARδ to induce transcription of the Pparg2 gene and, in doing so, promotes adipogenesis (21,41). In cardiomyocytes, KLF15 cooperates with PPARα in regulating lipid metabolism (42). Conversely, activation of GR signaling can induce a number of KLFs (e.g., KLF9, KLF11, and KLF15) in specific physiologic or pathologic contexts (43)(44)(45).…”
Section: Methodsmentioning
confidence: 99%
“…FAO rate was determined by release of ]-oleic acid as described previously (47). Glycolysis rate and mitochondrial respiration rate in NRVMs were assessed using a Seahorse XFp Extracellular Flux Analyzer with the XFp Glycolysis Stress Test Kit and the XFp Cell Mito Stress Test Kit, respectively (Seahorse Bioscience) (42). For in vitro autophagy studies, NRVMs were infected with indicated adenovirus for 72 hours, followed by treatment with 20 μmol/l CCCP with or without 100 nmol/l BFA for 2 hours (35) (CCCP, Sigma-Aldrich, C2759; BFA, Sigma-Aldrich, B1793).…”
Section: Methodsmentioning
confidence: 99%
“…Although all PPARs bind as heterodimers to their cognate DNA elements with the retinoid X receptor (RXR), they may also interact with other transcription factors. For instance, recent work has shown that the Kruppel-like factor 15 (KLF15) interacts directly with PPARα in the heart to regulate genes involved in FAO (Prosdocimo et al 2014(Prosdocimo et al , 2015.…”
Section: Biogenic Machinery: Transcriptional Networkmentioning
confidence: 99%
“…For instance, sirtuin 1 (Sirt1) has been shown to directly dimerize with PPARα, resulting in displacement of RXR and reduced fatty acid utilization (32). In addition, Krüppel-like factor 15 (KLF15) interacts directly with PPARα to cooperatively activate FAO gene expression (33). Loss of KLF15 results in reduced cardiac FAO rates and markedly reduced mitochondrial FAO gene expression (34).…”
Section: Brief Overview Of Cardiac Fuel and Energy Metabolismmentioning
confidence: 99%